Interprofessional collaboration to promote transportation equity for environmental justice populations: A mixed methods study of civil engineers, transportation planners, and social workers' perspectives. (May 2020) - Fields, Noelle L.; Miller, Vivian J.; Cronley, Courtney; Hyun, Kyung (Kate); Mattingly, Stephen P.; Khademi, Sheida; Nargesi, Saeed Reza Ramezanpour; Williams, Jessica
Abstract: This study explored engineers, planners, and social workers interactions around issues of transportation decision-making and transportation equity and identified opportunities for enhanced collaboration and training in anticipation of transformative technologies for environmental justice populations. The study assessed the current level of knowledge among professionals (engineers, planners, and social workers) about the training needs of the other professions under investigation and their own preparation for interprofessional collaboration in order to improve transportation equity for environmental justice populations. The study also identified the benefits and strategies for engineers, planners, and social workers in collaboration on transportation infrastructure and policy decisions. This study used a mixed methods, sequential exploratory design to gather information from engineers, planners, and social workers. The results showed that participants across all three professions saw a need to address the unmet and/or underserved transportation needs of environmental justice populations. Social workers identified advocacy and resource identification among some of the most important transportation-related skills while transportation experts reported data analysis and planning as key skills. The majority of study participants indicated that all three professions can greatly inform transportation planning and that interprofessional collaboration is important for improving and enhancing transportation planning. The participants cited limited interactions and siloed working environments as challenges to effective collaboration across the professions. The authors propose future research recommendations and training/education strategies for enhancing interprofessional collaboration around transportation equity for environmental justice populations. Highlights: Interprofessional and interdisciplinary work is critical to promoting livable communities. The focus of this study is to explore interprofessional collaborations to promote transportation equity. Participants reported a need to address the unmet/underserved transportation needs of environmental justice populations. Participants cited limited interactions and siloed working environments as challenges to effective collaboration. Study findings suggest that interprofessional collaboration is welcomed and needed.